Patogenicidade de bacillus thuringiensis sobre chrysodeixis includens Walker, 1857 (lepidoptera: noctuidae) - Sampaio, Amanda Roberta (2017)
Biological control has gained prominence in research because it is a natural means of decreasing populations of insect pests, especially with the use of the bacterium Bacillus thuringiensis (Bt). Therefore, it is considered an ecologically correct strategy to control the target species, most often with effectiveness, not attacking nature and being more selective to non-target populations. One of the pest of great importance in soybean and vegetable crops is Chrysodeixis includens Walker, 1857 (Lepidoptera: Noctuidae), popularly known as a false-moth caterpillar, considered difficult to control. In this context, the search for control strategies for C. includens is necessary, as well as the conduction of basic studies for the development of new products. In view of the above, the objective of this work was to identify molecularly and to evaluate the pathogenicity of isolates of B. thuringiensis, isolated from the soil, on C. includens. Soil samples for Bt isolation were collected at different points of the Universidade Tecnológica Federal do Paraná - Câmpus Dois Vizinhos / PR. These lines were kept refrigerated in petri dishes with agar-nutrient culture medium and periodically peeled. Before thepathogenicity evaluation, a pre-selection of the strains was done by means of molecular analysis, identifying the presence of cry1 and cry2 genes, using PCR (Polymerase Chain Reaction), where it was possible to select five samples that have the two genes, these being those tested in the bioassays with C. includens. The five strains were quantified and the spore counts viable were determined by the "microgota" technique, to determine the viable spores by adjusting the concentration of CFU used in the bioassays, which was on the order of 108 or 107. 50 μL of culture of each B. thuringiensis strain on the artificial diet surface for C. includens, previously distributed in 12-well cell culture plates, where one insect was placed per well using five dishes per treatment (n = 60 insects ). The evaluation was performed at 12, 24, 48 and 72 hours after the start of the bioassay, quantifying the number of dead caterpillars. Fourteen Bt strains isolated from the UTFPR soil samples were submitted to molecular analyzes, of which only five presented the cry1 and cry2 genes (EM41P, PR31P, FR31P, RR14P and PR11P). The five selectedstrains caused mortality ranging from 85% to 100% in second instar larvae of C. includens, at the end of 72 hours of evaluation, and did not differ significantly from the positive control. These results indicate a high bioinsecticidal potential of the new identified strains. Throughout the evaluation period the lineages caused similar mortalities to Dipel WP, not statistically differing from this, except for the PR11P lineage, which in the evaluation of 12 -hour mortality obtained a significant difference when compared to Dipel WP. Eleven of the fourteen strains isolated from the soil of UTFPR - Câmpus Dois Vizinhos have the cry2 gene. Five of them also had positive results for cry1 gene amplification and these, tested in bioassays showed high potential in the control of Chrysodeixis includens.